THE ROLE OF EMOTIONS IN PRAGMATICS (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This article explores pragmatics and the importance of emotions in pragmatic process. It is a complex and multifaceted topic that bridges cognitive science, philosophy, psychology, and linguistics. Pragmatics, in a general sense, refers to the study of how context influences the interpretation of language, and it extends to how speakers convey and interpret meaning in everyday communication. And this work also proposes to study different approaches of scholars and researches about this matter.